Legal Settlement of Fiduciary Guarantee Objects Transferred by Debtors to Third Parties - Setiyo Nugroho, Latif; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze: 1) The application of criminal sanctions against acts of transfer of fiduciary collateral. 2) Alternative non-litigation efforts in law enforcement against acts of transfer of fiduciary collateral. This type of research is normative legal research. The approach method in this study is the statute approach. The type of data in this study is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (study document). The analysis in this study is prescriptive. The results of the study concluded: 1) The application of criminal sanctions against the act of transferring fiduciary collateral without written consent from the creditor is a form of legal protection for creditor rights and an effort to uphold the principle of legal certainty in financing agreements. Based on Article 23 paragraph (2) and Article 36 of Law Number 42 of 1999 concerning Fiduciary Collateral, the act of transferring, pawning, or renting fiduciary collateral without written consent from the fiduciary recipient is categorized as a criminal act, with a maximum prison sentence of two years and a maximum fine of fifty million rupiah. The criminal elements in these provisions are alternative, so that the fulfillment of one form of action (transferring, pawning, or renting) without the creditor's consent is sufficient to ensnare the perpetrator criminally. The application of this provision can be seen in the Decision of the Jepara District Court No. 320/Pid.Sus/2011/PN Jpr, where the defendant was sentenced to prison and a fine for the act of re-pledged fiduciary objects without permission. 2) Alternative non-litigation efforts in law enforcement against acts of transfer of fiduciary collateral are effective and efficient means of law enforcement against acts of transfer of fiduciary collateral without the consent of the creditor. Settlement through non-litigation channels such as consultation, negotiation, mediation, conciliation, or expert assessment can be a solution that prioritizes the principles of justice, benefit, and efficiency of time and cost compared to a long criminal justice process.